2019
DOI: 10.1002/ptr.6493
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lycopene supplement on the spermatogram and seminal oxidative stress in infertile men: A randomized, double‐blind, placebo‐controlled clinical trial

Abstract: Infertility is a major, worldwide problem that is affected, and mediated, by several factors, in particular, oxidative stress. Thus, the aim of this study was to evaluate the effect of lycopene supplementation on spermatogram and seminal oxidative stress. In this randomized, double‐blind, placebo‐controlled trial study, 44 infertile men with oligozoospermia were randomly divided into two groups: The experimental group was supplemented with 25 mg of lycopene, and the control group received placebo for 12 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 45 publications
1
34
0
5
Order By: Relevance
“…Researchers have showed anomalies in sperm DNA methylation and homocysteine accumulation in men with infertility. As regards to high level folate and B12 in traditional and healthy dietary pattern and above mechanisms, this diet can prevent DNA damage and also improved sperm concentration and motility (32,37).studies showed increase oxidative stress level can effect on sperm motility and increase DNA fragmentation, also based on this finding, intake of antioxidants increases sperm concentration and improves its progressive motility (21,35).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Researchers have showed anomalies in sperm DNA methylation and homocysteine accumulation in men with infertility. As regards to high level folate and B12 in traditional and healthy dietary pattern and above mechanisms, this diet can prevent DNA damage and also improved sperm concentration and motility (32,37).studies showed increase oxidative stress level can effect on sperm motility and increase DNA fragmentation, also based on this finding, intake of antioxidants increases sperm concentration and improves its progressive motility (21,35).…”
Section: Discussionmentioning
confidence: 92%
“…In the case-control study, 400 infertile men according to approved andrologist's indices jointed to the case group of our study from July 2019 to December 2019. In case group, inclusion criteria included aged 20-55 years, a sperm count less than 15 million per milliliter, normal morphology less than 4%, sperm concentration less than 15 x 106 million, semen volume less than 1.5 ml and normal motility less than 40%, also exclusion criteria included chronic disease, testicular atrophy, ejaculatory disorder, hypospadiasis, stenosis, varicocele, adherence to specific diets, non-response to more than 35 items of food frequency questionnaire and underreporting and over-reporting of energy intake (less than 800 and more than 4,200) (20,21).…”
Section: Study Populationmentioning
confidence: 99%
“…In the literature, several non-enzymatic antioxidants, such as arginine, carnitine, carotenoids, coenzyme Q10, cysteine, reduced glutathione, micronutrients like selenium or zinc, vitamin E, vitamin C, myo-inositol, or resveratrol, have been reported to be utilized to treat different diseases [107]. In the case of ART, exogenous antioxidants have been tested for decades, and several works point out to a positive contribution of these supplements on sperm count, motility, and morphology [108][109][110]. Other studies have also proved that antioxidants are useful to ameliorate lipid peroxidation, reduce DNA base modifications (like 8-OHdG) and fragmentation, and increase total antioxidant capacity [111][112][113][114].…”
Section: Antioxidantsmentioning
confidence: 99%
“…We read with great interest the article entitled “The effects of lycopene supplement on the spermatogram and seminal oxidative stress in infertile men: A randomized, double‐blind, placebo‐controlled clinical trial” by Nouri et al (Nouri, Amani, Nasr‐Esfahani, & Tarrahi, ). This study investigated the effect of lycopene supplementation (25‐mg daily) for 12 weeks on spermatogram and seminal oxidative stress in males with oligozoospermia.…”
Section: Compliance With Ethical Standards Funding Informationmentioning
confidence: 99%